Javier Sicilia: Advocate of deliberative democracy in the Americas - Rathbun, Lyon (Annales. Etyka w Życiu Gospodarczym, 2019)
When Javier Sicilia’s son was killed by cartel assassins in 2011, he transformed into a civic activist, with a mass following sufficiently large for Time Magazine to recognize him in 2011 as one of its “Protestors of the Year.” His very success mobilizing public opinion against cartel violence overshadows his more fundamental role as an advocate for deliberative democracy in the Americas. Sicilia’s historical importance lies in his recognition that only civic dialogue within the transnational public sphere that includes Mexico and the United States can heal the social pathologies unleashed by globalization and by the war on drugs. His ultimate achievement has been to dramatize what would be required of citizens to realize the democratic ideals that both countries profess as the foundations of their national identities.